Time-Varying Formation of Heterogeneous Multiagent Systems via Reinforcement Learning Subject to Switching Topologies - Liu, Deyuan; Liu, Hao; Lu, Jinhu; Lewis, Frank L. (IEEE transactions on circuits and systems. I, Regular papers, 2023)
This paper investigates the optimal formation control of a heterogeneous multiagent system consisting of multiple quadrotors and ground vehicles via reinforcement learning to achieve the time-varying formation under switching topologies. A distributed observer is firstly constructed to generate references using local information for each vehicle to form time-varying formation and the convergence of the observer under switching topologies is proven. Then, reinforcement learning methods are provided for the heterogeneous vehicle group to realize the optimal tracking control without information of vehicle dynamical model. Simulation tests are given to confirm the effectiveness of the proposed method.